Hyperadrenocorticism Induces Demodicosis in Shih Tzu Dog - Maulana ArRaniri Putra; Cucu Kartini Sajuthi (ARSHI Veterinary Letters, 2017)
A 10-year old male intact Shih Tzu, was presented to our clinic with complains of skin and hair problem. The condition had been appeared for 3 months. The antifungal medicated shampoo was given to the patient by the previous veterinarian, but there was no any clinical improvement. The clinical symptoms included alopecia in the dorsal body and trunk, comedones, hyperpigmentation, scales, lichenification, pot bellied, polyuria and polydipsia. Skin scraping and trichogram in the face area and fore limb found Demodex sp. Adult onset generalized demodicosis usually has an underlying cause. Endocrine disorders such as hypothyroidism and hyperadrenocorticism must be ruled out. From the clinical sign and laboratory work suggested for Low Dose Dexamethasone Suppressing Test (LDDST). Cortisol value after 8 hours of low dose dexamethasone injection was greater than basal cortisol, it means dexamethasone failed to suppressing cortisol level due to the high number of cortisol in the body. From LDDST the diagnose of hyperadrenocorticism (Cushing syndrome) has been made. The dog was given trilostane (Vetoryl®) 3mg/kg SID for the Cushing and imidacloprid and moxidectine spot on (Advocate® spot on) every 2 weeks for the demodicosis. Scales and lichenification was reduced and the skin got better after 3 weeks. Unfortunately, after 3 months of treatment, the dog had neurological sign including seizure, head tilt and nystagmus. From the neurological sign, we suspected that the dog had macroadenoma type of hyperadrenocorticism. A week after hospitalization, the owner decided to euthanize the dog.